2020
DOI: 10.3390/ncrna6040042
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Long Non-Coding RNAs (lncRNAs) in Tumor Angiogenesis

Abstract: Long non-coding RNAs (lncRNAs) are defined as non-protein coding transcripts with a minimal length of 200 nucleotides. They are involved in various biological processes such as cell differentiation, apoptosis, as well as in pathophysiological processes. Numerous studies considered that frequently deregulated lncRNAs contribute to all hallmarks of cancer including metastasis, drug resistance, and angiogenesis. Angiogenesis, the formation of new blood vessels, is crucial for a tumor to receive sufficient amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 143 publications
(234 reference statements)
0
22
0
Order By: Relevance
“…LncRNAs have been proposed as important regulators of tumor angiogenesis, affecting tumor-associated cells, oncogenic pathways or binding to other RNA transcripts [ 6 ]. For instance, lncRNA HIF2PUT acts as a direct upstream promoter inducing EPAS1 (HIF2A) expression in colorectal cancer and consequently increasing angiogenesis; another example is the lncRNA PVT1, which stabilizes STAT3 and therefore indirectly increases VEGF expression in gastric cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been proposed as important regulators of tumor angiogenesis, affecting tumor-associated cells, oncogenic pathways or binding to other RNA transcripts [ 6 ]. For instance, lncRNA HIF2PUT acts as a direct upstream promoter inducing EPAS1 (HIF2A) expression in colorectal cancer and consequently increasing angiogenesis; another example is the lncRNA PVT1, which stabilizes STAT3 and therefore indirectly increases VEGF expression in gastric cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lncRNAs have attracted the attention of more and more researchers. 8 , 27 , 28 An increasing number of studies have reported that lncRNAs are dysregulated and are essential regulators and tumor facilitators in cervical cancer. 29 Hence, identifying the lncRNAs involved in cervical cancer and exploring their detailed roles will be beneficial for developing effective targets to guide cancer diagnosis, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been extensively studied and identified as novel modulators during carcinogenesis and cancer progression (10)(11)(12). The aberrant expression of lncRNAs has been widely discovered in human cancers, manifesting a close correlation with aggressive biological events (13)(14)(15). Several studies have demonstrated the crucial regulatory actions…”
Section: Introductionmentioning
confidence: 99%